Condition of Students' Mathematical Reasoning Abilities Based on Their Ability to Argue - Arlina Trie Cahyono; Susiswo Susiswo; Tjang Daniel Chandra (Universitas Negeri Malang, 2021)
This study aims to reveal the condition of students' reasoning abilities based on the way students argue. This research uses a qualitative-descriptive approach. The subjects in this study were 3 students of junior high school with high reasoning abilities and 3 students with low reasoning abilities who viewed the reasoning ability scores when providing problem solving solutions on the written test. The data obtained in this study were in the form of students' written test scores and the results of student interviews. Interviews were conducted to bring up students 'ability to argue that describe and reveal the condition of students' reasoning abilities in the process of solving problems. The results of students 'arguments are analyzed and adjusted to the model of StephenToulmin's argument which reveals that there are 6 components of the argumentation to show the seriousness of students in arguing in order to obtain valid argument results to assess students' reasoning abilities. The arguments from students succeeded in uncovering 4 conditions that describe the conditions of students' mathematical reasoning abilities. These conditions are: 1) Students who show high reasoning ability in written tests and are able to show their reasoning process in the arguments that are brought up, 2) Students who show low reasoning abilities in written tests but are able to show their reasoning processes in the arguments that are brought up, 3) Students which shows a high reasoning ability in a written test but have not been able to demonstrate the reasoning process in the arguments that are brought up, and 4) Students who show a low reasoning ability in a written test and have not been able to demonstrate their reasoning process in the arguments that are brought up.